ϕ production in In-In collisions at 158 A GeV - Arnaldi, Roberta; Banicz, K.; Borer, K.; Castor, J.; Chaurand, B.; Chen, W.; Cicalò, C.; Colla, A.; Cortese, P.; Damjanovic, S.; David, A.; Falco, A. de; et al. (Journal of physics. G, Nuclear and particle physics, 2010)
The NA60 experiment at the CERN SPS studied ϕ production in In-In collisions at 158 A GeV via muon and kaon decay channels. The yields and transverse mass spectra observed in the two channels are compatible within errors. The results are compared to the previous measurements in Pb-Pb collisions, where large discrepancies were observed between NA50 (muon pairs) and NA49 (kaon pairs).
Gesehen am 25.11.2022